Quantitative determination of the femoral offset templating error in total hip arthroplasty using a new geometric model. (10th October 2022) - Liechti, Emanuel F.; Attinger, Marc C.; Hecker, Andreas; Kuonen, Kim; Michel, Andrea; Klenke, Frank M.
Abstract : Aims: Traditionally, total hip arthroplasty (THA) templating has been performed on anteroposterior (AP) pelvis radiographs. Recently, additional AP hip radiographs have been recommended for accurate measurement of the femoral offset (FO). To verify this claim, this study aimed to establish quantitative data of the measurement error of the FO in relation to leg position and X-ray source position using a newly developed geometric model and clinical data. Methods: We analyzed the FOs measured on AP hip and pelvis radiographs in a prospective consecutive series of 55 patients undergoing unilateral primary THA for hip osteoarthritis. To determine sample size, a power analysis was performed. Patients' position and X-ray beam setting followed a standardized protocol to achieve reproducible projections. All images were calibrated with the KingMark calibration system. In addition, a geometric model was created to evaluate both the effects of leg position (rotation and abduction/adduction) and the effects of X-ray source position on FO measurement. Results: The mean FOs measured on AP hip and pelvis radiographs were 38.0 mm (SD 6.4) and 36.6 mm (SD 6.3) (p < 0.001), respectively. Radiological view had a smaller effect on FO measurement than inaccurate leg positioning. The model showed a non-linear relationship between projected FO and femoral neck orientation; at 30° external neck rotation (with reference to the detector plane), a true FO of 40 mm was underestimated by up to 20% (7.8 mm). With a neutral to mild external neck rotation (≤ 15°), the underestimation was less than 7% (2.7 mm). The effect of abduction and adduction was negligible. Conclusion: For routine THA templating, an AP pelvis radiograph remains the gold standard. Only patients with femoral neck malrotation > 15° on the AP pelvis view, e.g. due to external rotation contracture, should receive further imaging. Options include an additional AP hip view with elevation of the entire affected hip to align the femoral neck more parallel to the detector, or a CT scan in more severe cases. Cite this article: Bone Jt Open  2022;3(10):795–803.